2019
DOI: 10.1002/jcla.23109
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic profiling of amniotic fluid and its application in fetal lung maturity prediction

Abstract: Background:The pulmonary surfactant especially lipids in amniotic fluid can reflect the development stage of fetal lung maturity (FLM). However, the conventional lecithin/sphingomyelin (L/S) ratio method by thin layer chromatography (TLC) is insufficient and inconvenient for FLM prediction in clinical practice. Methods:The amniotic fluid samples were collected from the pregnant women in labor or undergoing amniocentesis and analyzed for its lipid contents with the liquid chromatography coupled with high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Pulmonary surfactants comprise approximately 90% of lipids (Cao et al. 2020 ), and PC is the most abundant. Changes in surfactant lipids on bacterial LPS have been reported (Deng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary surfactants comprise approximately 90% of lipids (Cao et al. 2020 ), and PC is the most abundant. Changes in surfactant lipids on bacterial LPS have been reported (Deng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lung surface active substances account for about 90% of lipids, of which PC is the most abundant and has some innate immunoreactivity [ 36 , 37 ]. In this study, we found that the metabolism of intracellular PC (22:4(7Z,10Z,13Z,16Z)/14:1(9Z)) was disturbed after RSV infection, which could be significantly regulated and brought to normal levels after treatment with LJF.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the lecithin/sphingomyelin (L/S), ratio by this layer chromatography was a conventional method for measuring surfactants in amniotic fluid. A high L/S ratio is associated with increasing gestational weeks as the sphingomyelin concentration remains relatively constant, while lecithin concentration increases during late pregnancy (Cao et al, 2020).…”
Section: Analysis Of Maximum Fs-50 Value Associated With Infant Asphy...mentioning
confidence: 99%